THE VERBALIZATION OF THE CONCEPT OF “FEAR” IN ENGLISH AND UZBEK PHRASEOLOGICAL UNITS (British Journal of Global Ecology and Sustainable Development, 2023)
The significance and importance of lexical and semantic analysis of the lexical field denoting negative emotions has been a core subject of the study in recent years to define thoroughly its role and essence in linguistics, to be precise, in acquisition properly. Although “Fear” tends to be associated with negative affect, the phenomenological field in this regard is often poorly differentiated. This article is devoted to the study of English and Uzbek phraseological units related to the emotional concept of “fear”. The article presents a sample of these phraseological units, compares them, and analyses the inner form of the concept of “fear” in the selected phraseological units.